Individual criminal responsibility for crimes against humanity: A juridical analysis of the decisions of the international criminal court - Havez, Muhammad (Ex Aequo Et Bono Journal Of Law, 2026)
Background: Crimes against humanity are among the gravest offences under international criminal law and require individual criminal responsibility to prevent impunity. The International Criminal Court (ICC), established by the Rome Statute, provides a framework on crimes against humanity and modes of liability, yet its case law reveals doctrinal tensions. This article examines how the Court interprets and applies individual criminal responsibility in such cases. Methods: The research employs a normative legal method using statute and case approaches. It analyses provisions of the Rome Statute on crimes against humanity and individual responsibility, and reviews selected ICC judgments, which are qualitatively assessed to evaluate coherence and trends in the Court’s reasoning. Findings: The study finds that the Court has developed an architecture of modes of liability, including direct perpetration, co-perpetration, indirect perpetration, participation, and command responsibility, each with distinct actus reus and mens rea requirements. However, overlaps between modes, fluctuating evidentiary thresholds for senior leaders, and divergences between Trial and Appeals Chambers generate uncertainty and raise concerns about consistency and fairness. These dynamics reveal a gap between the conceptual aims of international criminal law and its practical enforcement before the ICC. Conclusion: The article concludes that, although the Court has advanced the doctrine of individual criminal responsibility for crimes against humanity, significant doctrinal and practical challenges remain. Novelty/Originality of this article: This study offers a structured mapping of modes of liability in ICC jurisprudence and links those patterns to wider debates on the legitimacy and effectiveness of international criminal justice.